Analisis Bentuk Kekerasan pada Anak dalam Novel Bayang Suram Pelangi Karya Arafat Nur - Miftahul Jannah; Mukhlis Mukhlis; Muhammad Iqbal (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study entitiled “Analysis of Forms of Violence in Children in Arafat Nur's Novel Bayang Suram Pelangi". The problem in this researchd is how the forms of violence against children in the novel Bayang Suram Pelangi by Arafat Nur. The purpose of this study was to determine the form of violence against children in Arafat Nur's novel Bayang Suram Pelangi. This research uses a qualitative approach. The data source of this research is the novel by Arafat Nur, namely Bayang Suram Pelangi (2018). Data collection was carried out using documentation techniques. Data analysis was done qualitatively by reading the novel repeatedly, then describing or explaining the forms of violence contained in the novel comprehensively. The resultsd showed that there were four forms of violence, namely physical violence which was carried out by hitting and kicking, psychological violence which caused fear, worry, helplessness, and insecurity, verbal violence which was carried out using harsh words, insults, and threats, social violence perpetrated by exclusion. Of the four forms of violence, the most dominant thing experienced by child characters is psychological violence.